AN EVALUATION OF THE CORPORATE ENVIRONMENT FOR THE FORMATION OF ITS EFFECTIVE EXPANSION STRATEGY - B. G, KOLORIYO (International Journal of Multidisciplinary Research and Studies, 2020)
The successful development of a company’s expansion strategy, which determines the most effective corporate performance, is especially full of its environment which is defined by multidimensional assessment criteria acting in numerous directions. The incorporation of all such criteria into one generalizing and sophisticated dimension is enabled by multi-criteria assessment methods. The article focuses on the theoretical justification for the appliance of multi-criteria evaluation methods and their application in identifying the particular and forecast environmental situation of the corporate and provides an answer for the formation of an efficient expansion strategy using the complex evaluation results of the corporate environment. Through the examination of a particular company by employing the probabilities of the proposed analytical solution the expansion strategy is made for effective development.